PROTO-RIPARIAN GOVERNANCE AND WATER SOVEREIGNTY IN THE AL- TARIKH SALASILAH NEGERI KEDAH - Mohd Firdaus Abdullah; Shaiful Shahidan; Nurhidayu Rosli; Al-Amril Othman (SEJARAH: Journal of the Department of History, 2025)
This article reinterprets Al-Tarikh Salasilah Negeri Kedah as an early record of proto-riparian governance in the Malay world. Moving beyond palace-centred readings that treat the text as a mere genealogy of kingship, the study situates it within the broader history of environmental law and political sovereignty in Southeast Asia. It argues that the Al-Tarikh Salasilah Negeri Kedah preserves traces of indigenous water governance in the form of customary norms regulating access, maintenance, and territorial demarcation. Episodes of river excavation, the drawing of boundaries, and the collective management of waterways are interpreted as expressions of early juridical consciousness embedded within the political imagination of the Kedah court. The article identifies three foundational dimensions of this proto-riparian system. First, water functioned as a legal commons that defined social obligation and responsibility within the community. Second, rivers and canals operated as instruments of territorialisation through which rulers inscribed authority upon the landscape. Third, collective labour in water projects served as a mechanism of governance linking royal command with communal stewardship. These dimensions reveal a coherent framework of customary water law that predates colonial codifications and challenges the assumption that the regulation of water in Malaysia began under British administration. By positioning the Al-Tarikh Salasilah Negeri Kedah as an indigenous archive of environmental jurisprudence, the article reframes Malay historiography beyond ritual symbolism towards the study of legal and ecological institutions. It argues that water management in early Kedah embodied both sovereignty and moral responsibility, creating a local moral economy of flow that continues to resonate within debates on resource rights, federal–state relations, and environmental justice in contemporary Malaysia.